Propiedades psicométricas de un instrumento de las competencias genéricas del egresado de una universidad privada de Cali, Colombia (2012)
This article describes the development and validation of an instrument to assess the self-perception of generic competencies in graduates of a private university in the city of Cali, Colombia. Initially, the common competences from 11 undergraduate careers were selected based on the review of academic programs, empirical and theoretical backgrounds. Then, competencies were defined to build the instrument, which was evaluated by 11 expert judges, in a process of content validation. The questionnaire was applied to 22 graduates of undergraduate programs in a pilot application. Subsequently, it was applied to a sample of 574 graduates of the 11 careers, obtaining a final instrument composed of 33 generic competencies. A Cronbach alpha coefficient of 0.912 was obtained and all 33 items were accepted.